MENINGKATKAN PRESTASI BELAJAR MATEMATIKA PADA SISWA KELAS V MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE - Siti Haeriah (Universitas Muhammadiyah Makassar, 2021)
This study aims to determine the improvement of students' mathematics learning outcomes through the TPS type cooperative learning model. This type of research is classroom action research. The research subjects consisted of 32 students which were carried out in 2 cycles, namely cycle 1 and cycle 2. Students' mathematics learning outcomes increased through the Think Pair Share Cooperative Learning Model. This can be seen from the learning outcomes of the first cycle which are in the medium, with an average score of 59.22 from the ideal score of 100.00, an increase in the category in the second cycle which is in the high category with an average score of 72.97 of the score. ideally 100.00. Students' motivation to learn Mathematics has increased through the Think Pair Share Cooperative Learning Model. This increase can be seen from the experience of students, attention, and activeness of students in the teaching and learning process in accordance with the results of observations during implementation actions and from the results of student reflections.